Identifikasi Penyediaan Air Bersih oleh PDAM Tirta Medal dalam Melayani Rumah Sakit Umum di Kabupaten Sumedang - Mujahidah Nur Fauziah Mulyadi; Hani Burhanudin (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. Sumedang Regency has 3 General Hospital Units, including Sumedang Hospital, Pakuwon General Hospital, and Harapan Keluarga Hospital. Sumedang Hospital is planned to be developed by increasing the number of beds. In addition, there is a general hospitals that will operate, namely Berlian Kasih General Hospital and Harapan Keluarga Hospital which have not been served by the PDAM Tirta medal. The purpose of this study is to identify the amount of clean water provided by the PDAM Tirta Medal in serving clean water for General Hospitals in the Sumedang Regency. The method used in this research is a descriptive quantitative analysis and then projects the results using arithmetic methods. Based on the existing conditions, the scale of clean water distribution services managed by PDAM Tirta Medal has covered 15 sub-districts which are divided into four regions. The results of the projection analysis show that the supply of clean water in Region I will only be available for 6 years if during that time PDAM Tirta Medal does not further develop its clean water supply because the supply discharge is quite small. Meanwhile, in Region II the supply projection will increase again until 2038, the projected supply discharge is 244.04 m3/day Abstrak. Kabupaten Sumedang memiliki 3 Unit Rumah Sakit Umum, diantaranya RSUD Sumedang, RSU Pakuwon, dan RSU Harapan Keluarga. RSUD Sumedang direncanakan akan dikembangkan dengan menambah jumlah bed. Selain itu, terdapat Rumah Sakit Umum yang akan beroperasi, yaitu Rumah Sakit Umum Berlian Kasih serta RSU Harapan Keluarga juga belum terlayani oleh PDAM Tirta medal. Tujuan dari penelitian ini yaitu untuk mengidentifikasi jumlah penyediaan air bersih PDAM Tirta Medal dalam melayani air bersih untuk Rumah Sakit Umum yang berada di Kabupaten Sumedang. Metode yang digunakan pada penelitian ini berupa analisis kuantitatif deskriptif kemudian memproyeksikan hasilnya menggunakan metode aritmatika. Berdasarkan kondisi eksisting, skala pelayanan distribusi air bersih yang dikelola PDAM Tirta Medal telah mencakup 15 kecamatan yang dibagi ke dalam empat wilayah. Hasil analisis proyeksi menunjukan bahwa penyediaan air bersih di wilayah I hanya akan tersedia selama 6 tahun apabila dalam jangka waktu tersebut PDAM Tirta Medal tidak mengembangkan lagi penyediaan air bersihnya karena debit penyediaan yang cukup kecil. Sementara pada wilayah II proyeksi penyediaan akan naik kembali hingga tahun 2038, debit proyeksi penyediaanyya sebesar 244,04 m3/hari.